Soil structure and soil organic matter in water-stable aggregates under different application rates of biochar - Simansky, Vladimir; Horak, Jan; Juriga, Martin; Srank, Dusan (Vietnam Journal of Earth Sciences, 2018)
The effects of biochar and biochar combined with N-fertilizer on the content of soil organic matter in water-stable aggregates were investigated. A field experiment was conducted with different biochar application rates: B0 control (0 t ha-1), B10 (10 t ha-1) and B20 (20 t ha-1) and 0 (no N), 1st and 2nd levels of nitrogen fertilization on silt loam Haplic Luvisol (Dolna Malanta, Slovakia), in 2014. The N doses of level 1 were calculated on required average crop production using balance method. Level 2 included additional 100% of N in year 2014 and additional 50% of N in year 2016. The effects were investigated during the growing seasons of spring barley and spring wheat in 2014 and 2016, respectively. Results indicate that the B20N2 treatment significantly increased the proportion of water-stable macro-aggregates (WSAma) and reduced water-stable micro-aggregates (WSAmi). Aggregate stability increased only in the B20N1 treatment. The B20N2 treatment showed a robust decrease by 27% in the WSAma of 0.5-0.25 mm. On the other hand, an increase by 56% was observed in the content of WSAma with fractions 3-2 mm compared to the B0N0 treatment. The effect of N fertilizer on WSAma was confirmed only in the case of the B10N2 treatment. The proportion of WSAma with fractions 3-2 mm decreased by 42%, while the size fraction of 0.5-0.25 mm increased by 30% compared to the B10N0 treatment. The content of WSAma with fractions 1-0.5 mm decreased with time. On the contrary, the content of WSAma with particle sizes above 5 mm increased with time in all treatments except the B10N2 and B20N2 treatments. A statistically significant trend was identified in the proportion of WSA in the B10N2 and B20N2 treatments, which indicates that biochar with higher application levels of N fertilizer stabilizes the proportion of water-stable aggregates. In all treatments, the content of soil organic carbon (SOC) and labile carbon (CL) in WSAmi was lower than those in WSAma. A considerable decrease of SOC in the WSAma >5 mm and an increase of SOC in WSAmi were observed when biochar was applied at the rate of 10 t ha-1. Contents of SOC in WSAmi increased as a result of adding biochar combined with N fertilizer at first level. CL in WSA significantly increased in all size fractions of WSA.References Abiven S., Hund A., Martinsen V., Cornelissen G., 2015. Biochar amendment increases maize root surface areas and branching: a shovelomics study in Zambia. Plant Soil, 342, 1-11. Agegnehu G., Bass A.M., Nelson P.N., and Bird M.I., 2016. Benefits of biochar, compost and biochar–compost for soil quality, maize yield and greenhouse gas emissions in a tropical agricultural soil. Sci. Tot. Environ., 543, 295-306. Angers D.A., Samson N., Legere A., 1993. Early changes in water-stable aggregation induced by rotation and tillage in a soil under barley production. Can. J. Soil Sci., 73, 51-59. Atkinson Ch.J., Fitzgerald J.D., Hipps N.A., 2010. Potential mechanisms for achieving agricultural benefits from biochar application to temperate soils: a review. Plant Soil, 337, 1-18. Balashov E., Buchkina N., 2011. Impact of short- and long-term agricultural use of chernozem on its quality indicators. Int. Agrophys., 25, 1-5. Barrow C.J., 2012. Biochar: potential for countering land degradation and for improving agriculture. Appl. Geogr., 34, 21-28. Barthes B.G., Kouakoua E.T., Larre-Larrouy M.C., Razafimbelo T.M., De Luca E.F., Azontonde A., Neves C.S.V.J., De Freitas P.L., Feller C.L., 2008. Texture and sesquioxide effects on water-stable aggregates and organic matter in some tropical soils. Geoderma, 143, 14-25. Benbi D.K., Brar K., Toor A.S., Sharma S., 2015. Sensitivity of labile soil organic carbon pools to long-term fertilizer, straw and manure management in rice-wheat system. Pedosphere, 25, 534-545. Benbi D.K., Brar K., Toor A.S., Singh P., Singh H., 2012. Soil carbon pools under poplar-based agroforestry, rice-wheat, and maize-wheat cropping systems in semi-arid India. Nutr. Cycl. Agroecosys., 92, 107-118. Blanco-Canqui H., Lal L., 2004. Mechanisms of carbon sequestration in soil aggregates. Crit. Rev. Plant Sci., 23, 481-504. Brevik E.C., Cerda A., Mataix-Solera J., Pereg L., Quinton J.N., Six J., Van Oost K., 2015. The interdisciplinary nature of SOIL. SOIL, 1, 117-129. Brodowski S., John B., Flessa H., Amelung W., 2006. Aggregate-occluded black carbon in soil. Eur. J. Soil Sci., 57, 539-546. Bronick C.J., Lal R., 2005. The soil structure and land management: a review. Geoderma, 124, 3-22. Chenu C., Plante A., 2006. Clay-sized organo-mineral complexes in a cultivation chronosequece: revisiting the concept of the “primary organo-mineral complex”. Eur. J. Soil Sci., 56, 596-607. Dziadowiec H., Gonet S.S., 1999. Methodical guide-book for soil organic matter studies.  Polish Society of Soil Science, Warszawa, 65p. Elliott E.T., 1986. Aggregate structure and carbon, nitrogen, and phosphorus in native and cultivated soils. Soil Sci. Soc. Am. J., 50, 627-633. Fischer D., Glaser B., 2012. Synergisms between compost and biochar for sustainable soil amelioration, In: Kumar S. (ed.): Management of Organic Waste, In Tech Europe, Rijeka, 167-198. Glaser B., Lehmann J., Zech W., 2002. Ameliorating physical and chemical properties of highly weathered soils in the tropics with charcoal - a review. Biol. Fertil. Soils., 35, 219-230. Heitkotter J., and B. Marschner, 2015. Interactive effects of biochar ageing in soils related to feedstock, pyrolysis temperature, and historic charcoal production. Geoderma, 245-246, 56-64. Herath H.M.S.K., Camps-Arbestain M., Hedley M., 2013. Effect of biochar on soil physical properties in two contrasting soils: an Alfisol and an Andisol. Geoderma, 209-210, 188-197. Hillel D., 1982, Introduction to soil physics. Academic Press, San Diego, CA , 364 p. Chenu C., Plante A., 2006. Clay-sized organo-mineral complexes in a cultivation chronosequence: revisiting the concept of the “primary organo-mineral complex”. Eur. J. Soil Sci., 56, 596-607. IUSS Working Group WRB., 2014. World reference base for soil resources 2014. International soil classification system for naming soils and creating legends for soil maps. World Soil Resources Reports, 106, FAO, Rome., 112p. Jeffery S., Verheijen F.G.A., Van der Velde M., Bastos A.C., 2011. A quantitative review of the effects of biochar application to soils on crop productivity using meta-analysis. Agr. Ecosys. Environ., 144, 175-187. Jien S.H., Wang Ch.S., 2013. Effects of biochar on soil properties and erosion potential in a highly weathered soil. Catena, 110, 225-233. Kammann C., Linsel S., Goßling J., Koyro H.W., 2011. Influence of biochar on drought tolerance of Chenopodium quinoa Willd and on soil-plant relations. Plant Soil, 345, 195-210. Kodesova R., Nemecek K., Zigova A., Nikodem A., Fer M., 2015. Using dye tracer for visualizing roots I pact on soil structure and soil porous system. Biologia, 70, 1439-1443. Krol, A., Lipiec, J.,  Turski, M., J. Kuoe, 2013. Effects of organic and conventional management on physical properties of soil aggregates. Int. Agrophys., 27, 15-21. Kurakov A.V., Kharin S.A., 2012. The Formation of Water-Stable Coprolite Aggregates in Soddy-Podzolic Soils and the Participation of Fungi in This Process. Eur. Soil Sci., 45, 429-434. Loginow W., Wisniewski W., Gonet S.S., Ciescinska B., 1987. Fractionation of organic carbon based on susceptibility to oxidation. Pol. J. Soil Sci., 20, 47-52. Lynch, J.M., and E. Bragg, 1985. Microorganisms and soil aggregate stability. Adv. Soil Sci., 2, 133-171. MHYPERLINK "about:blank"unkholm L.J., Schjonning P., Debosz K., Jensen H.E., Christensen B.T., 2002. Aggregate strength and mechanical behaviour of a sandy loam soil under long-term fertilization treatments. Eur. J. Soil Sci., 53, 129-137. Paradelo R., Van Oort F., Chenu C., 2013. Water-dispersible clay in bare fallow soils after 80 years of continuous fertilizer addition. Geoderma, 200-201, 40-44. Purakayastha T.J., Kumari S., Pathak H., 2015. Characterisation, stability, and microbial effects of four biochars produced from crop residues. Geoderma, 239-240, 293-303. Rees F., Germain C., Sterckeman T., Morel J.L., 2015. Plant growth and metal uptake by a non-hyperaccumulating species (Lolium perenne) and a Cd-Zn hyperaccumulator (Noccaea caerulescens) in contaminated soils amended with biochar. Plant Soil, 395, 57-73. Saha D., Kukal S.S., Sharma S., 2011. Land use impacts on SOC fractions and aggregate stability in typic Ustochrepts of Northwest India. Plant Soil, 339, 457-470. Six J., Bossuyt H., Degryze S., Denef  K., 2004. A history of research on the link between (micro)aggregates, soil biota, and soil organic matter dynamics. Soil Till. Res., 79, 7-31. Six J., Elliott E.T., Paustian K., 2000. Soil macroaggregate turnover and microaggregate formation: A mechanism for C sequestration under no-tillage agriculture. Soil Biol. Biochem., 32, 2099-2103. Soinne H., Hovi J., Tammeorg P., Turtola E., 2014. Effect of biochar on phosphorus sorption and clay soil aggregate stability. Geoderma, 219-220, 162-167. Simansky V., 2013. Soil organic matter in water-stable aggregates under different soil management practices in a productive vineyard. Arch. Agron. Soil Sci., 59(9), 1207-1214. Simansky V., Jonczak J., 2016. Water-stable aggregates as a key element in the stabilization of soil organic matter in the Chernozems. Carp. J. Earth Environ. Sci., 11, 511-517. Simon T., Javurek M., Mikanova O., Vach M., 2009. The influence of tillage systems on soil organic matter and soil hydrophobicity. Soil Till, Res., 105, 44-48. Tiessen H., Stewart J.W.B., 1988. Light and electron microscopy of stainedmicroaggregates: the role of organic matter and microbes in soil aggregation. Biogeochemistry, 5, 312-322. Tisdall J.M., Oades J.M., 1980. The effect of crop rotation on aggregation in a red-brown earth. Austr. J. Soil Res., 18, 423-433. Vadjunina A.F., Korchagina Z.A., 1986. Methods of Study of Soil Physical Properties. Agropromizdat, Moscow, 415p. Vaezi A.R., Sadeghi S.H.R., Bahrami H.A., Mahdian M.H., 2008. Modeling the USLE K-factor for calcareous soils in northwestern Iran. Geomorphology, 97, 414-423. Von Lutzow M., Kogel-Knabner I., Ekschmitt K., Matzner E., Guggenberger G., Marschner B., Flessa H., 2006. Stabilization of organicmatter in temperate soils:mechanisms and their relevance under different soil conditions a review. Eur. J. Soil Sci., 57, 426-445.